Seasonal variability of trace elements bioaccumulation in Pacific Oyster (Cassostrea gigas) from an experimental pilot farm in the Calich Lagoon (Sardinia Italy) - Domenico Meloni; Alessandro Graziano Mudadu; Maria Cesarina Abete; Anna Maria Bazzoni; Alessandra Griglione; Rosa Avolio; Simonetto Serra; Nicola Fois; Giuseppe Esposito; Rita Melillo; Stefania Squadrone (Journal of Trace Elements in Medicine and Biology, 2024)
Background: Metals pollution is a worldwide environmental issue due to their persistence in the ecosystems, nondegradability, and bioaccumulation in marine biota. Pacific Oysters (Crassostrea gigas) are highly nutritious bivalve representing an important dietary constituent but may accumulate metals through feeding on suspended sediments from surrounding water, then represent a suitable tool for biomonitoring. Materials and methods: The occurrence of trace elements (Al, As, Cd, Co, Cr, Cu, Fe, Mn, Mo, Ni, Pb, Rb, Se, Sn, V, Zn) was investigated in Pacific Oysters (Cassostrea gigas) collected from Calich Lagoon in each season of 2019. Samples were homogenized and subjected to microwave acid digestion before being analyzed by inductively coupled plasma-mass spectrometer (ICP-MS). Results: The results showed a significant seasonal variation for temperature, dissolved oxygen, chlorophyll, and pH. Moreover, high significant seasonal variation in concentrations of Cd, Mn, Ni, and V was recorded. The highest values were found for Fe (128 mg kg−1 w.w.), and Al (112 mg kg−1 w.w.) in October, for Zn (113 mg kg−1 w.w.) in March and May. Conclusions: Pacific Oysters were confirmed as suitable bioindicators of the health status of coastal lagoons; trace elements concentrations were highly affected by season of collection, and according to literature the highest values were recorded in autumn and summer. The EU legal limits for Cd and Pb were not exceeded, then the farmed oysters were safe to consumers